Relationship between thrust, anthropometrics, and dry-land strength in a national junior swimming team - Morais, Jorge (2019)
Objectives: This study aimed to (i) assess an anthropometric and thrust inter-limb asymmetry, and; (ii) determine the contribution of anthropometrics, and dry-land upper-body strength and power to the thrust of talented adolescent swimmers.Methods: Eighteen talented adolescent swimmers (12 boys and 6 girls: 15.81 ± 1.62 years old) were evaluated. A set of anthropometric, dry-land upper-body strength and power, and in-water thrust were assessed.Results: Despite the fact that the dominant side presented higher values in anthropometrics (except for the hand surface area) and thrust, non-significant inter-limb differences were found. The symmetry index indicated a symmetry between upper-limbs. Hierarchical linear modeling retained as main predictors of each upper-limb thrust the respective hand surface area (dominant upper limb: estimate = 0.293, 95CI: 0.117; 0.469, p = 0.005; non-dominant upper limb: estimate = 0.295, 95CI: 0.063; 0.526, p = 0.025). The full stroke cycle retained the upper-body dry-land strength as main predictor (estimate = 0.397, 95CI: 0.189; 0.605, p = 0.002).Conclusion: The hand surface area and upper-body strength were the main predictors of each upper-limb and full stroke cycle thrust, respectively. Hence, coaches and practitioners should aim to carefully maximize the hand surface area (by finger spreading) while performing the stroke, as well as dry-land upper-body strength in order to enhance the performance.